BENTUK KERJASAMA PUBLIC-PRIVATE PEMBANGUNAN GRAVING DOCK DAN MANAJEMEN GALANGAN KAPAL DENGAN METODE ANALYTICAL HIERARCHI PROCESS (AHP) - Hartono Hartono; Arif Hidayat; Jati Utomo Dwi H (Diponegoro University, 2013)
In paper Development of port infrastructure in Indonesia is now no longer the responsibility of centralgovernment, along with limited funds and the government's insistence seaport infrastructure needs. Toaccelerate economic growth, the government issued Government Regulation as a legal umbrella. The purpose ofthis study was to examine public-private partnership opportunities in the construction of graving dock andshipyard management. Targets do is review, the criteria are prioritized cooperation and cooperationpriorities.This study used qualitative and quantitative approach, a descriptive qualitative approach throughinterviews used to assess the normative aspect. The quantitative approach used to assess the priority criteriaforms of cooperation and public-private partnership in development graving dock and shipyard management byusing the Analytical Hierarchy Process (AHP). Based on the AHP analysis can be concluded that the expertsdisagree about the priority criteria of cooperation, where the majority of them choose the duration as the maincriterion. As for the analysis of priorities of the cooperation of all experts choose Built-Operate-Transfer (BOT),which is deemed suitable for long-term investment of up to 30 years. BOT puts private partners to more freely tofinance, construct, operate, anticipated rate of return on capital (rate of return) and the risks of commercial andregulatory aspects